2017
DOI: 10.1007/s11302-017-9572-5
|View full text |Cite
|
Sign up to set email alerts
|

Injury-induced purinergic signalling molecules upregulate pluripotency gene expression and mitotic activity of progenitor cells in the zebrafish retina

Abstract: Damage in fish activates retina repair that restores sight. The purinergic signalling system serves multiple homeostatic functions and has been implicated in cell cycle control of progenitor cells in the developing retina. We examined whether changes in the expression of purinergic molecules were instrumental in the proliferative phase after injury of adult zebrafish retinas with ouabain. P2RY messenger RNA (mRNA) increased early after injury and showed maximal levels at the time of peak progenitor cell prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…We observed that the injury following exposure to CoCl 2 , which targeted and killed virtually all photoreceptors, accelerated the induction and rate of progenitor proliferation activity, peaking between 72 and 96 hpl. In contrast, when the injury was caused with a single injection of ouabain (either at a low, medium or high dose), the Müller glia‐derived progenitor proliferative peak was observed at 5–7 dpl (Fimbel et al., ; Medrano et al., ; Sherpa et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed that the injury following exposure to CoCl 2 , which targeted and killed virtually all photoreceptors, accelerated the induction and rate of progenitor proliferation activity, peaking between 72 and 96 hpl. In contrast, when the injury was caused with a single injection of ouabain (either at a low, medium or high dose), the Müller glia‐derived progenitor proliferative peak was observed at 5–7 dpl (Fimbel et al., ; Medrano et al., ; Sherpa et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A single intravitreal injection of ouabain at low concentrations damages inner retina cells (Fimbel et al., ), whereas higher doses of ouabain provoke cell death across all retina layers, including RPE and choroid cells (Medrano et al., ; Sherpa et al., ). In contrast, injury with intense light causes photoreceptor death as the original and principal effect (Rajaram et al., ; Weber et al., ; Wu et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, there are various retinal neuronal injury paradigms used in zebrafish research. Undoubtedly, the most common of those paradigms is light-induced retinal degeneration [ 86 , 90 , 91 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 ], followed by chemically [ 95 , 103 , 155 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 ] or mechanically induced retinal damage [ 92 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 ]. The choice of paradigm depends on the desired outcome, for example, ouabain has a more global retinal degenerative effect (depending on concentration), while intense light exposure primarily affects the photoreceptors [ 156 , 169 ].…”
Section: Neuroprotection and Regeneration In Zebrafish Retinal Injmentioning
confidence: 99%
“…Interestingly, the extracellular nucleotide agonist, ADPβS, induced the expression of lin28a and ascl1a genes in mature regions of uninjured retinas. This gene expression was inhibited by blocking the early injury-induced activation of P2RY1, which also prevented progenitor cell proliferation [ 181 ]. Sonic hedgehog (shh) was also found to be upregulated after ouabain injury, and treating the retina with shh resulted in Müller cell hypertrophy followed by their conversion to retinal progenitor cells [ 169 ].…”
Section: Neuroprotection and Regeneration In Zebrafish Retinal Injmentioning
confidence: 99%